Neural circuit mechanisms for steering control in walking Drosophila - Aleksandr Rayshubskiy; Stephen L Holtz; Alexander S Bates; Quinn X Vanderbeck; Laia Serratosa Capdevila; Victoria Rockwell; Rachel Wilson (eLife, 2025)
Orienting behaviors provide a continuous stream of information about an organism’s sensory experiences and plans. Thus, to study the links between sensation and action, it is useful to identify the neurons in the brain that control orienting behaviors. Here, we describe descending neurons in the Drosophila brain that predict and influence orientation (heading) during walking. We show that these cells have specialized functions: whereas one cell type predicts sustained low-gain steering, the other predicts transient high-gain steering. These latter cells integrate internally directed steering signals from the head direction system with stimulus-directed steering signals from multimodal sensory pathways. The inputs to these cells are organized to produce ‘see-saw’ steering commands, so that increasing output from one brain hemisphere is accompanied by decreasing output from the other hemisphere. Together, our results show that internal and external drives are integrated to produce descending motor commands with different timescales, for flexible and precise control of an organism’s orientation in space.